2000
DOI: 10.3989/cyv.2000.v39.i3.850
|View full text |Cite
|
Sign up to set email alerts
|

Corrosión atmosférica de metales en condiciones climáticas extremas

Abstract: Es conocido que el proceso de corrosión de metales expuestos a la atmósfera es de tipo electroquímico. Este proceso de corrosión tiene lugar cuando la superficie se encuentra humedecida debido a diferentes fenómenos meteorológicos como la lluvia, condensación de humedad (rocío), niebla, etc. El tiempo durante el cual permanece humedecida la superficie metálica, conocido como tiempo de humectación (TDH), es, por tanto, un factor determinante de la velocidad de corrosión atmosférica. Un indicador frecuentemente … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…Low temperatures cause the metallic surface to be covered with an ice layer for long time periods during the year, considerably impeding the development of corrosion processes. This ice layer reduces oxygen access to the metallic surface and its time of wetness, decreasing corrosion rates to extremely low values [ 28 , 29 , 30 , 31 ]. In stations characterised as rural environments where SO 2 and Cl − deposition rates have not been determined due to being insignificant, values have been estimated for both pollutants.…”
Section: Methodsmentioning
confidence: 99%
“…Low temperatures cause the metallic surface to be covered with an ice layer for long time periods during the year, considerably impeding the development of corrosion processes. This ice layer reduces oxygen access to the metallic surface and its time of wetness, decreasing corrosion rates to extremely low values [ 28 , 29 , 30 , 31 ]. In stations characterised as rural environments where SO 2 and Cl − deposition rates have not been determined due to being insignificant, values have been estimated for both pollutants.…”
Section: Methodsmentioning
confidence: 99%
“…Authors dedicated to the study of corrosion [2][3][4][5][6][7][8] demonstrated that different metals exposed to coastal atmosphere increases the speed of this process much more than if they were influenced by another type of atmosphere; NaCl was identified as an atmospheric pollutant of the most aggressive for corrosion to occur. This salt is incorporated from the sea being its profound effects near the shore, where air transports large amounts and produces a continuous water spray [9] It was, noted further, that the presence of circulating liquid media do through structures, mainly at medium temperatures and different chemical compositions, resulting also highly corrosive under these conditions [2].…”
Section: Introductionmentioning
confidence: 99%
“…El proceso de corrosión de metales expuestos a la atmósfera es de tipo electroquímico; tiene lugar cuando la superficie se encuentra humedecida, debido a diferentes fenómenos meteorológicos, como la lluvia, la condensación de humedad en el ambiente y la niebla (Chico et al 2000).…”
Section: Introductionunclassified